(untitled) (Innovative professional education, 2022)
The article examines the issue of test control learning technology; itsadvantages over established methods of pedagogical control: the scientific validity ofthe test, which provides an objective assessment; manufacturability of the test method;measurement accuracy; the presence of the same requirements for all subjects;compatibility of test technology with other pedagogical technologies